Reprodução em cativeiro de piracanjuba Brycon orbignyanus assistida por marcador molecular como estratégia de conservação - Oliveira, Daniela José de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The freshwater fauna of fish in Brazil is particularly diverse and a lot of these species that compose it are not naturally found elsewhere. Such diversity has a high number of stocks in natural watercourses, which have suffered significant reduction as a result of uncontrolled exploitation of resources, because the capture of juveniles, overfishing, lack of supervision and protectionist measures, water pollution, introduction of exotic species, and especially by the increasing fragmentation of rivers by the construction of hydroelectric projects, which modify the collective spawning areas and disrupt the migratory path of some species. Currently listed on the official list of endangered species (IN on 4/2005) 196 fish species, of which 141 from freshwater, among which seven are considered overfished. Among the migratory fish species classified as endangered by IUCN, the Brycon is the most represented in the Red Book of Endangered Fauna (MMA, 2008), with six endangered species, and piracanjuba Brycon orbignyanus is among them. Brycon orbignyanus is a reofílico fish because migrate long distances to breed and, therefore, does not reproduce naturally in captivity environment. Between management actions to reduce the impacts of human activities on fish stocks, can highlight a ban on fishing during the breeding period , control of fishing , prohibiting the use of certain fishing equipment , programs and build fishways fish . However, many of these strategies and actions for improvement or maintenance of natural resources has been made without scientific backing, simply based on common sense. This study aims to conduct captive breeding of B. orbignyanus different source locations, assisted by genetic analysis of mitochondrial DNA and also molecular microsatellite markers in order to produce genetically juvenile suitable for use in management programs . For genetic analysis, total DNA was obtained from samples of animal tissue collected from ...

A fauna de peixes de água doce no Brasil é particularmente diversa e muitas das espécies que a compõem não são encontradas naturalmente em outros locais. Tal diversidade contém um número elevado de estoques naturais nos cursos d’água, os quais vêm sofrendo sensível redução como resultado da exploração desordenada dos recursos, devido a captura de indivíduos jovens, pesca predatória, falta de fiscalização e medidas protecionista, poluição das águas, introdução de espécies exóticas e, principalmente, pela crescente fragmentação dos rios devido à construção de empreendimentos hidroelétricos, que modificam as áreas de desova coletiva e interrompem o trajeto migratório de algumas espécies. Atualmente constam na lista oficial de espécies ameaçadas de extinção (IN no 4/2005) 196 espécies de peixes, sendo que 141 são de água doce, entre as quais sete são consideradas sobreexplotadas. Dentre as espécies de peixes migradoras classificadas em perigo pela IUCN, o gênero Brycon é o mais representado no Livro Vermelho da Fauna Ameaçada de Extinção (MMA, 2008), com seis espécies ameaçadas, sendo que a piracanjuba Brycon orbignyanus consta entre elas. Brycon orbignyanus é um peixe reofílico, pois migra por longas distâncias para se reproduzir e, sendo assim, não se reproduz naturalmente em ambiente de cativeiro. Entre as ações de manejo que visam reduzir os impactos das ações antrópicas sobre os estoques de peixes, pode-se destacar a proibição da pesca durante o período de reprodução, controle da pesca, proibição do uso de determinados equipamentos de pesca, programas de repovoamento e a construção de mecanismos de transposição de peixes. Porém, muitas destas estratégias e ações para melhoria ou manutenção dos recursos naturais têm sido realizadas sem respaldo cientifico, com base simplesmente no senso comum. Este estudo tem como objetivo principal realizar a reprodução em ...
Keywords: Peixe de agua doce; Peixe - População; Genetica de populações; Biodiversidade - Conservação; Brycon; Biodiversity conservation